the Developing Assessment Instrument In Critical Thinking Ability For Fifth Grade Of Elementary School In Thematic Learning - Hartanto, Hartanto; Rusilowati, Ani; Kartono, Kartono (Journal of Research and Educational Research Evaluation, 2019)
The background of this study is about the availibility of the test assessment instrument to measure the critical thinking ability of fifth grade elementary school students which is limitted. Therefore, it needs to be developed. This development research used the Borg & Gall development method. The purpose of this study was to develop an assessment instrument in essay. The assessment instrument was validated by 5 Experts Judgment by using the Aiken'V formula. The results of trials using the construct validity of the Confirmatory Factor Analysis (CFA), interater reliability used Two Ways Anova proved by the Ebel formula and internal consistent reliability with the Alpha Cronbach formula. The result of expert judgment validation showed that Ã¢â€°Â¥0.8 which mean that 10 items were in valid category, construct validity results from large-scale test analysis by using LISREL 8.8 namely Confirmatory Factor fulfilled the testing of goodness of fit GFI value 0,93, CFI=0,97 and NFI=0,91. The three assessment criteria have value > 0,90. It can be concluded that the construct validity is met. The construct validity is also evidenced by the loading factor of 10 items. All of which have a price of > 0,3. The interrater reliability assessment instruments based on Expert Judgment coefficient value was 0,62. The expert agreement indicated that the rating given by each rater is reliable or consistent between one another and internal consistency of small scale test results of coefficient value of alpha 0,861, large scale 0.813. Practicality of assessment instruments based on expert judgment had mean 37.2 and included in practical category. The profile of critical thinking skills of fifth grade elementary school students category Ã¢â‚¬Å“MediumÃ¢â‚¬Â. The Conclusions was the assessment instruments in critical thinking skills of fifth grade students on thematic learning were tested in validity, reliability and suitable to be used.